2020
DOI: 10.1101/2020.11.28.402032
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

De novoactivated transcription of inserted foreign coding sequences is inheritable in the plant genome

Abstract: The manner in which newborn genes become transcriptionally activated and fixed in the plant genome is poorly understood. To examine such processes of gene evolution, we performed an artificial evolutionary experiment in Arabidopsis thaliana. As a model of gene-birth events, we introduced a promoterless coding sequence of the firefly luciferase (LUC) gene and established 386 T2-generation transgenic lines. Among them, we determined the individual LUC insertion loci in 76 lines and found that one-third of them w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 77 publications
(116 reference statements)
0
9
0
Order By: Relevance
“…We found analogous cases in transgenic plants, in which promoterless LUC genes became transcriptionally activated concomitant with chromatin remodelling around the LUC insertion loci (Kudo, Matsuo, and Satoh et al ., 2020; Hata and Takada et al ., 2020). From the massive analysis of transgenic cultured cells, we also found that transcriptional activation occurred stochastically at 30% of the insertion events across the genome and was independent of chromosomal loci, suggesting that this transcriptional activation reflects the stochastic nature of chromatin remodelling (Satoh and Hata et al ., 2020). Taken together, these findings suggest that gene insertion events stochastically activate local chromatin remodelling to form a transcription-competent chromatin configuration.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…We found analogous cases in transgenic plants, in which promoterless LUC genes became transcriptionally activated concomitant with chromatin remodelling around the LUC insertion loci (Kudo, Matsuo, and Satoh et al ., 2020; Hata and Takada et al ., 2020). From the massive analysis of transgenic cultured cells, we also found that transcriptional activation occurred stochastically at 30% of the insertion events across the genome and was independent of chromosomal loci, suggesting that this transcriptional activation reflects the stochastic nature of chromatin remodelling (Satoh and Hata et al ., 2020). Taken together, these findings suggest that gene insertion events stochastically activate local chromatin remodelling to form a transcription-competent chromatin configuration.…”
Section: Discussionmentioning
confidence: 92%
“…To scrutinize the manner in which newborn promoters occur in the plant genome, we analysed the transcription start sites (TSSs) of previously established transgenic A. thaliana T87 cell lines that harboured exogenously inserted promoterless luciferase ( LUC ) genes (Satoh and Hata et al ., 2020). Because the cells experienced only 5–10 somatic cell divisions without luciferase-based screening, we assumed that they had retained the characteristic features of newborn genes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations